Study of variation in microRNA regions and early head development in Arctic charr (Salvelinus alpinus) - Vanesa Calvo Baltanás 1990- (2012)
ABSTRACT Arctic charr (Salvelinus alpinus) is a northern freshwater fish that inhabits the sea, lakes and rivers. In Iceland those lakes have been all formed after the last glaciation (10000 years ago). In Lake Thingvallavatn, Iceland, Arctic charr shows as many as four sympatric morphs. Two of them are limnetic (Planktivorous and Piscivorous) and the rest are benthonic (Small benthic and Large benthic). One remarkable feature is the high variability these morphs present regarding to their morphology, behaviour and life history. One part of this research will be focused on the study of genetic variation in different microRNAs genomic region of Planktivorous (PL), Small Benthic (SB) and Large Benthic (LB) population. These regions will also be compared between Salmo salar and Salvelinus alpinus. Another aim is to study the developmental basis of morphological differences observed in the three morphs previously mentioned plus one more, an Aquaculture (AC) stock. The main goal is to describe eye size, position and shape changes along variation in the strucutures of the splacnocranium in early stages of these morphs. After that different morphs and stages will be compared, ossification of these structures will be also explained comparing morphs and stages. Samples used in the study of genetic variation where collected in different years from Lake Thingvallavatn, in Iceland. DNA isolation, amplification by PCR procedure and sequencing were done in order to identify and describe variations in the miRNA regions. Once these variations were found, I tested for genotype and allele frequency differences between morphs. Using morphometrics, I tested morph/stage differences in changes of the structures. In conclusion significant allele and genotype frequency between morphs were found comparing LB with SB and PL in the microRNA genomic region of 19c,20b-3p,18b and 18b*. Embryos used for morphometrics had the bigger stage frame for AC. Comparison was possible in 4 stages of the four morphs finding significant differences ...